Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar IPAS Siswa Kelas V SD Negeri 060828 Medan - Wardhani, Siska; Tamba, Robenhart (Indonesian Journal Publisher, 2025)
This study aims to measure the effect of the application of the Problem Based Learning (PBL) learning model on the learning outcomes of fifth-grade students at Medan State Elementary School 060828. The study was conducted at Medan State Elementary School 060828 in the even semester of the 2024/2025 academic year. The design used in this study is the One-Group Pretest-Posttest Design, which is included in quantitative research with a quasi-experimental approach. This design involves one group of subjects without a control group as a comparison. The population in this study includes all fifth-grade students of Medan State Elementary School 060828, totaling 30 students. Data collection techniques used are observation, interviews, tests, and documentation. The research instrument used is a multiple-choice test to measure students' learning outcomes in science. The results show that the application of the Problem Based Learning (PBL) model has a significant effect on improving student learning outcomes. This is proven through the results of the hypothesis test, where the significance value was recorded as less than 0.05 (p < 0.001) with a calculated t value greater than the t table. Thus, the null hypothesis (H₀) is rejected, while the alternative hypothesis (Hₐ) is accepted. These findings indicate that the implementation of the PBL model significantly contributes to improving student learning outcomes in Natural and Social Sciences (IPAS) subjects.